2006
DOI: 10.1111/j.1365-2966.2006.11128.x
|View full text |Cite
|
Sign up to set email alerts
|

The coronal structure of Speedy Mic – II. Prominence masses and off-disc emission*

Abstract: Observations of stellar prominences on young rapidly rotating stars provide unique probes of their magnetic fields out to many stellar radii. We compare two independently obtained data sets of the K3 dwarf Speedy Mic (BO Mic, HD 197890) using the Anglo‐Australian Telescope (AAT) and the European Southern Observatory (ESO) Very Large Telescope (VLT). Taken more than a fortnight apart, they provide the first insight into the evolution of the prominence system on such a young rapidly rotating star. The largest pr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
30
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 25 publications
8
30
0
Order By: Relevance
“…Cameron & Robinson 1989) and Speedy Mic (Dunstone et al 2006a) and are often observed as transient absorption features passing through the Doppler‐broadened Hα stellar line. Recently, however, an analysis of Very large Telescope data of Speedy Mic by Dunstone et al (2006b) has revealed rotationally modulated emission outside the stellar Hα line due to loops of emission seen off of the stellar disc, but which can also be associated with prominences seen to transit the stellar disc at other times. In addition, peculiar low‐velocity emission features seen in SS Cyg and IP Peg during outburst have also been interpreted as ‘slingshot prominences’ (Steeghs et al 1996).…”
Section: A Slingshot Prominence?mentioning
confidence: 99%
“…Cameron & Robinson 1989) and Speedy Mic (Dunstone et al 2006a) and are often observed as transient absorption features passing through the Doppler‐broadened Hα stellar line. Recently, however, an analysis of Very large Telescope data of Speedy Mic by Dunstone et al (2006b) has revealed rotationally modulated emission outside the stellar Hα line due to loops of emission seen off of the stellar disc, but which can also be associated with prominences seen to transit the stellar disc at other times. In addition, peculiar low‐velocity emission features seen in SS Cyg and IP Peg during outburst have also been interpreted as ‘slingshot prominences’ (Steeghs et al 1996).…”
Section: A Slingshot Prominence?mentioning
confidence: 99%
“…At later evolutionary stages, solar type stars are still seen to have extended, suspended material: the 50 Myr old (Luhman et al 2005) solar analog AB Dor was observed to have cool, corotating clouds at distances from ∼9-20 R * from the rotation axis, and were estimated to have masses 10 18 g (Collier Cameron & Robinson 1989). Dunstone et al (2006) observed prominences on Speedy Mic, a 30 Myr old K3 dwarf, and estimated masses to be ∼2×10 17 g. In stellar outflows, the Alfvén radii are typically comparable to or slightly larger than the size of the largest closed magnetic loops (e.g., Mestel & Spruit 1987). Thus, the measured sizes of postflare loops and prominences may represent an approximate lower limit on the Alfvén radii for these systems.…”
Section: What Is the Magnetic Lever Arm Length?mentioning
confidence: 99%
“…Both studies found prominences at or above the corotation radius of the star. The Hα profile in the present data set is studied in a separate publication (Dunstone et al 2005), revealing a densely packed prominence system beyond the corotation radius.…”
Section: Introductionmentioning
confidence: 98%